2011
DOI: 10.1111/j.1399-0012.2011.01491.x
|View full text |Cite
|
Sign up to set email alerts
|

Access to living donor transplantation for Aboriginal recipients: a study of living donor presentation and exclusion

Abstract: Aboriginals experience high rates of end-stage renal disease (ESRD) and are less likely to receive a kidney transplant from a living donor. We hypothesized that higher rates of hypertension and diabetes in Aboriginal communities would result in fewer potential living donors coming forward and more exclusions for medical reasons. We performed a retrospective study to examine the frequency of potential donor presentation and the reasons for donor exclusion among Aboriginal and Caucasian wait-listed ESRD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Furthermore the median duration for transplant evaluation was 954 days compared to 596 days in Caucasians. In a recent study from Manitoba, Aboriginal potential donors were often excluded due to non-medical reasons, such as loss of contact [6]. Our findings are consistent with previous studies and further demonstrate reduced Aboriginal deceased and living donor transplantation is not limited to the Prairie Provinces alone.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore the median duration for transplant evaluation was 954 days compared to 596 days in Caucasians. In a recent study from Manitoba, Aboriginal potential donors were often excluded due to non-medical reasons, such as loss of contact [6]. Our findings are consistent with previous studies and further demonstrate reduced Aboriginal deceased and living donor transplantation is not limited to the Prairie Provinces alone.…”
Section: Discussionsupporting
confidence: 90%
“…Decreased rates of both living and deceased donor transplants have been documented in various regions across Canada, and the largest international study to date indicates Aboriginals receive transplants at roughly half the rate compared to the Caucasian ESRD population [6,7]. There are many theories that have been postulated as to why this discrepancy exists such as a decrease in living donors, residing in remote communities or low socioeconomic status but to date no clear reasons have been brought to the forefront.…”
Section: Introductionmentioning
confidence: 99%
“…Given that many of the studies guiding these recommendations are based on Caucasian donors, Canadian transplant programs should be cautious in generalizing these results given the ethnic diversity of our population. Although the prevalence of living kidney donation and transplantation in the Canadian Indigenous population is low, 10 medical clearance must consider the unique pathophysiology in this group. Diabetes mellitus has a more aggressive course in Indigenous peoples and the incidence of associated ESRD and death is higher compared to non-Indigenous Canadians.…”
Section: Review Processmentioning
confidence: 99%
“…Another Australian study on waitlisting and access to kidney transplantation found that being Indigenous, a woman, or living in rural and remote regions was significantly associated with a lower likelihood of waitlisting for kidney transplant [ 12 ]. In another kidney transplant study examining the disparity in access to living donors for Aboriginal patients in Australia, researchers found that while most potential donors for non-Aboriginal recipients would be excluded for medical reasons such as hypertension or diabetes, potential donors to Aboriginal recipients were significantly more likely to be excluded for nonmedical reasons, most due to loss of contact [ 13 ]. In addition to a relative paucity of studies that focus on the liver, solid organ transplantation equity research tends to focus on disparities in referral, waitlisting, and outcomes, with little inquiry into the foundational factors such as systemic and structural racism creating and perpetuating these disparities.…”
Section: Introductionmentioning
confidence: 99%